Culture of Lawfulness and Human Rights. Indigenous community property in the Interamerican Court of Human Rights’ judgments - Candia Falcón, Gonzalo; Muñoz Villalobos, Alonso (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The present article aims to analyze the relationship between the culture of legality and the Inter-American System of Human Rights. The authors argue that the decisions of the Inter-American Court of Human Rights can positively influence the development of the culture of legality within the States Parties, provided that they meet certain Rule of Law requirements. The body of decisions developed by the Court, regarding indigenous property rights, is analyzed to precisely illustrate how judgments —which do not sufficiently realize basic requirements of legal certainty and determination—, finally limit the positive impact that those decisions may produce for any national culture of legality.